Prey selection and foraging behavior of Eriocheir sinensis towards three freshwater mollusk species: Mechanisms and ecological implications - Yanming Sui; Aijia Lin; Weiwei Su; Weiyi Zou; Yiyun Zhang; Linlan Lv; Hucheng Jiang (Behavioural Processes, 2026)

Metagenomic insights into the global distribution and functional potentials of major polyphosphate-accumulating organisms (PAOs) in activated sludge wastewater treatment plants - Zhenhui Yang; Yi Yang; Daliang Ning; Xiaomin Fan; Yiqing Lv; Linlan Zhuang; Linwei Wu (Water Research, 2026)

Enrichment Characteristics of Microplastics and Heavy Metals Accumulated in Bivalves in South Yellow Sea - Yingying Zhang; Wanjun Feng; Xuexing Dong; Yanming Sui; Linlan Lv (Bulletin of Environmental Contamination and Toxicology, 2026)

Impacts of Spartina alterniflora Control Measures on Wetland Aquatic Communities: eDNA-Based Diversity Responses of Fish and Zooplankton - Yanming Sui; Yanan Wei; Wanjun Feng; Dagui Liao; Cong Yan; Jiyi Chen; Linlan Lv (Wetlands, 2025)

RETRACTED: Li et al. Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus. Fishes 2024, 9, 407 - Lei Li; Chenshan Shao; Guodong Xv; Linlan Lv; Jiacheng Jiang; Weiyi Zou; Weiwei Su; Yanming Sui; Mei Jiang (Fishes, 2025)
The journal retracts the article titled “Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus” [...]

Microplastic Ingestion by Fish with Different Feeding Habits from Different Habitats in a Typical Semi-Enclosed Haizhou Bay - Yanming Sui; Yingying Zhang; Shihao Chen; Yangyang Shi; Jiaxin Zou; Mohsen Mohamed; Kunyun Qin; Yebing Yu; Zhiquan Liu; Liang Zheng; Linlan Lv (Journal of Ocean University of China, 2025)

Muti-Biomarker Approach and IBR Index to Evaluate the Oxidative Stress of Nanoplastic on the Clams, Meretrix meretrix and Sinonovacula constricta - Linlan Lv; Wanjun Feng; Ke Sun; Weihong Zhao; Fengjuan Jiang; Mohsen Mohamed; Lei Li; Yue Yang; Yingying Zhang; Yanming Sui; Xuexing Dong (Journal of Ocean University of China, 2025)

Enrichment characteristics of microplastics in Antarctic benthic and pelagic fish and krill near the Antarctic Peninsula - Linlan Lv; Wanjun Feng; Jiaying Cai; Yingying Zhang; Jiacheng Jiang; Dagui Liao; Cong Yan; Yanming Sui; Xuexing Dong (Science of The Total Environment, 2024)

RETRACTED: Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus - Lei Li; Chenshan Shao; Guodong Xv; Linlan Lv; Jiacheng Jiang; Weiyi Zou; Weiwei Su; Yanming Sui; Mei Jiang (Fishes, 2024)
The toxic effect and differences of Cr(VI) on superoxide dismutase (SOD) activity, MDA, and metallothionein (MT) content in the hepatopancreas and gill of Portunus trituberculatus were investigated during Cr(VI) enrichment (15 days) and release experiments (15 days). Results showed that the 1.50 and 0.30 mg/L test groups significantly exhibited higher SOD, MDA, and MT content in the hepatopancreas and gill compared with the control group after 15 days of enrichment (p 0.05). The gill of P. trituberculatus achieved the highest SOD activity, MDA, and MT content earlier than the hepatopancreas, but the highest values were lower. The gill showed a shorter recovery time than the hepatopancreas. We concluded that the gill of P. trituberculatus exhibited a more rapid response to, and recovery from, Cr(VI) exposure compared to the hepatopancreas, making it a more sensitive tissue for assessing Cr(VI) toxicity, though both tissues showed a capacity for recovery after the removal of the contaminant.

Investigation of physiological energetic response of the thick shell mussel, Mytilus coruscus, to microplastics and low salinity: Potential countermeasures to multi-environmental changes - Yanming Sui; Zhiyi Xue; Shihao Chen; Huimin Jiang; Yang Zhou; Haidang Nguyen; Linlan Lv; Cuihua Wang; Longyu Liu; Tianqi Cao; Shengmao Zhang; Liang Zheng (Aquaculture, 2023)

Habitual feeding patterns impact polystyrene microplastic abundance and potential toxicity in edible benthic mollusks - Senyang Wang; Liang Zheng; Mengyan Shen; Longsheng Zhang; Yiting Wu; Guangyu Li; Chuanbo Guo; Cunzhi Hu; Mingming Zhang; Yanming Sui; Xuexing Dong; Linlan Lv (Science of The Total Environment, 2023)

The Combined Effect of Plastic Particles Size and Concentration on Rotifers’ (Brachionus plicatilis) Performance - Yanming Sui; Senyang Wang; Mohamed Mohsen; Longsheng Zhang; Mengyan Shen; Zhiquan Liu; Haidang Nguyen; Shengmao Zhang; Kaixing Li; Linlan Lv; Xuexing Dong (Journal of Ocean University of China, 2022)

Effects of Ocean Acidification and Microplastics on Microflora Community Composition in the Digestive Tract of the Thick Shell Mussel Mytilus coruscus Through 16S RNA Gene Sequencing - Liguo Yang; Linlan Lv; Haojie Liu; Miaorun Wang; Yanming Sui; Youji Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Dietary lipid concentrations influence growth and chemical and fatty acid compositions of juvenile redlip mullet, Liza haematocheila - Wenping Yang; Aimin Wang; Feng Gao; Yebing Yu; Linlan Lv; Fu Lv (Aquaculture International, 2015)